Comparative study and geographical distribution of key protected wild vascular plants in Jiangxi Province, China - WAN Pingping1, WANG Lisong1*, WU Shaodong1, XIE Minghua2 (Guangxi Zhiwu)
Rare and endangered wild plants are important strategic resources and an essential component of biodiversity conservation. Grasping the diversity and geographic distribution of key protected plants in Jiangxi Province is a key step in developing scientific conservation and management at the provincial scale. Combining The List of National Key Protected Wild Plants(NKPWP, 2021)and The Checklist of the Key Protected Wild Plants in Jiangxi Province(KPWP, 2005), and digitized distribution data of herbarium specimens provided by the National Specimen Information Infrastructure(NSII), the diversity, geographic distribution, and conservation profile of these plants found in Jiangxi Province are analyzed. The results are as follows:(1)A total of 148 species of NKPWP(including intraspecies taxa), spanning 89 genera and 47 families, are found in Jiangxi Province.(2)A total of 407 species, belonging to 85 families and 208 genera, are recognized as the key protected plants in Jiangxi Province, including 16 species of lycopods and ferns(9 families and 10 genera); 26 species of gymnosperms(6 families and 17 genera), and 365 species of angiosperms(70 families and 181 genera).(3)Among of these species, 60.9% of them are protected within 32 national and provincial natural reserves; 70.5% of them are conserved ex situ in 67 Chinese botanic gardens.(4)Observation value and estimation value of species richness indicate that the areas with higher species richness include mountains and its adjacent areas of Lushan, Jiuling, Wugong, Jinggang in northern area, and Dayuling, Jiulian, and Wuyi in southern area. The distribution pattern of hotspots is generally consistent with the ranges of five key protected areas of biodiversity conservation in Jiangxi Province. The issues of the species included in The Checklist of the Key Protected Wild Plants of Jiangxi Province(2005)were discussed, and the 6E principles of the priority selection of key protected wild plants at province level and the related suggestions to strengthen the research on provincial protected plants were proposed.